Kinetic Interface Sensitive Tracers: Experimental Validation in a Two‐Phase Flow Column Experiment. A Proof of Concept. Issue 12 (26th December 2018) - Tatomir, A.; De Vriendt, K.; Zhou, D.; Gao, H.; Duschl, F.; Sun, F.; Licha, T.; Sauter, M.
Abstract: The quantification of the interfacial area between fluids in a multiphase system in porous media has been a subject of growing interest in disciplines where mass transfer across fluid interfaces is of importance. In this study, a proof of concept for a novel kinetic interface sensitive (KIS) tracer is provided by employing a simple, low‐cost, well‐controlled dynamic column experiment in conjunction with a macroscale two‐phase flow reactive transport model. The steel column is filled with a well‐characterized porous medium consisting of well‐sorted normally distributed glass beads ( d 50  = 240 μm). KIS tracers were designed to determine the specific interfacial area, a wn, between a nonwetting fluid and a wetting fluid, by evaluating the chemical reaction rates and mass transfer across the fluid‐fluid interface. This study shows for the first time a general framework behind the use of KIS tracers and their potential in assessing the a wn for a known capillary pressure‐saturation relationship under laboratory conditions. A two‐phase flow four‐component reactive transport and a two‐phase flow two‐component transport numerical model were developed to simulate the oil flooding of the initially water saturated column and tracer breakthrough curves obtained from experimental data. These breakthrough curves were subsequently used to approximate a wn using a polynomial relationship. The interpretation of the KIS tracer column experiments indicates that the range for maximum value of a wn is between 500 and 540 m 2 /m 3 . The results also show that despite the use of two independently synthesized tracers, if the reaction kinetics are well quantified, similar a wn values can be obtained. Key Points: This study shows for the first time the potential of KIS tracers in assessing the specific fluid‐fluid interfacial area in dynamic conditions Two numerical models were developed and used to simulate the oil flooding of the column and the KIS tracer breakthrough KIS tracers may supplement other methods of determining interfacial areas and be valuable in testing the thermodynamically multiphase flow theories